KELAYAKAN REHABILITASI MANGROVE DENGAN TEKNIK GULUDAN DALAM PERSPEKTIF PERDAGANGAN KARBON DI KAWASAN HIJAU LINDUNG MUARA ANGKE, PROVINSI DKI JAKARTA - Isluyandari Woelan Yanuartanti; Cecep Kusmana; Ahyar Ismail (Graduate School Bogor Agricultural University (SPs IPB), 2015)
Mitigation of climate change due to CO2 emissions, the forestry sector developed a REDD+ scheme. This study was conducted to examine financial feasibility of the mangrove rehabilitation with guludan technique, so that further funding of mangrove rehabilitation can be included into REDD+ scheme. Guludan technology was developed to overcome the deep water column for mangrove rehabilitation in the former pond area. This technique has been developed for mangrove species Avicennia marina with spacing 0.25 m x 0.25 m, 0.5 m x 0.5 m, and 1 m x 1 m. Based on diameter and height growth of 36 months planted seedlings of A.marina followed logistic model. CO2 sequestration 386.34 t/ha, 131.12 t/ha, and 26.75 t/ha in 0.25 m x 0.25 m, 0.5 m x 0.5 m, and 1 m x 1 m spacing. With CO2 sequestration selling price of €20,00/t CO2 and rehabilitated land area of 10 ha, this rehabilitation action using guludan technique is not financially feasible, because the criteria for a negative NPV, Net B/C< 1, and IRR < the investment rate, which is 12%. The alternative for this is by implementing material efficiency and increasing carbon selling price as much €54.5/t CO2 for the spacing 0.25 m x 0.25 m; €122/t CO2 for the spacing 0.5 m x 0.5 m; and €580/t CO2 for the spacing 1 m x 1 m.Keywords: Avicennia marina, guludan, CO2 sequestration, plant spacing, and financial feasibility